Analyzing laterally loaded piles in multi-layered cohesive soils: a hybrid beam on nonlinear Winkler foundation approach with case studies and parametric study - Mahmoud El Gendy (Discover Civil Engineering)
Abstract Pile foundations frequently encounter lateral loads originating from various hazards. These types of foundations are commonly utilized in structures like bridges, retaining walls, and high-rise buildings. Analyzing laterally loaded piles presents a complex geotechnical problem that entails considering multiple interrelated design factors. It requires accounting for structural bending behavior, soil–structure interaction, soil nonlinearity, and optimizing for cost-effectiveness. In this paper, the commonly used approach beam on nonlinear Winkler foundation is developed. This methodology involves representing the pile using one-dimensional finite elements in the vertical direction, incorporating nonlinear bending stiffness. Additionally, soil deformation is determined using empirically derived P-y curves, which are obtained from full-scale field tests. By combining the pile stiffness with the soil stiffness considering the full interaction between the pile and the surrounding soil, the complete stiffness matrix of the single pile is formed, leading to a reduction in the number of equations that need to be solved. Both Euler and Timoshenko beams are considered, and the analysis is conducted using both finite elements and finite difference methods. The proposed hybrid approach is validated by comparing its results from analyzing laterally loaded piles in multi-layered soil profiles with those obtained from different models in existing literature and available field measurements. The well-known software ELPLA is equipped with the proposed hybrid technique. Furthermore, a parametric study investigates the behavior of laterally loaded pipe piles in soft and stiff clay, culminating in the presentation of dimensionless curves from this study.